OPTIMIZATION OF POLYSACCHARIDE-RICH FRACTIONATION FROM MORINDA CITRIFOLIA L. FRUIT BASED ON IMMUNOSTIMULATORY EFFECT IN VITRO - Sasmito, Ediati; Hertiani, Triana; Kartika, Senda; Putri, Faradhyta Maharani; Setiawan, Vania; Narastika, Longina (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
Morinda citrifolia L. fruits are rich in polysaccharides of which are non toxic and possess hospes-mediated-antitumor potential. In Indonesia, noni fruit has been used empirically to enhance immune system. Previous research revealed that noni polysaccharide-rich fraction showed macrophage activity enhance-ment. This research aimed to optimize the method of noni-polysaccharides-rich fractionation using four different methods for polysaccharide isolation (method I, II, III, IV) and to evaluate the immunostimulatory effects of the isolated polysaccharides on macrophages and lymphocytes activities. Immunostimulatory effects were examined on male Balb/c mice in vitro. The polysaccharides were evaluated by phenol sulfuric acid test. Qualitative methods were used to detect the phytochemical characteristic. Total phenolic content was determined by using Folin-Ciocalteau method. The study showed different methods resulted in different yields, phytochemical characteristics and immunostimulatory activities of polysaccharides-rich fraction. The phytochemical test from method I, III and IVb revealed the presence of alkaloid. Method II resulted fractions with the presence of saponin. There were no protein and phenolic substances detected from all methods. The highest result of polysaccharide content was found in method IVb (32.58%). Method III showed the highest activity on phagocytic activity of the macrophage, while method IVb exhibited the highest stimulation on lymphocyte proliferation.Key words: Isolation method, polysaccharide, Morinda citrifolia L. immunostimulatory effect